Differentiated Thyroid Cancer in Children and Adolescents: 12-year Experience in a Single Center - Francisca Marques Puga; Laura Correia; Inês Vieira; Joana Serra Caetano; Rita Cardoso; Isabel Dinis; Alice Mirante (Galenos Yayincilik, 2024)
INTRODUCTION: Differentiated thyroid cancer (DTC) is the most common pediatric endocrine cancer but studies are scarce. Latest recommendations advocate for an individualized risk-based approach to select patients for additional therapy. Lymphovascular invasion is not considered, despite being a well-known risk factor in the adult population. The aim of this study was to describe the outcomes of a cohort of DTC patients diagnosed at pediatric age and to evaluate the impact of lymphovascular invasion on the risk of persistence/recurrence. METHODS: A retrospective study of patients diagnosed with DTC at pediatric age from 2010 to 2022 at a single center was performed. All patients had total thyroidectomy. Radioactive iodine therapy (RAI) was used in selected patients. The response to therapy and occurrence of persistent/recurrent disease were evaluated. RESULTS: A total of 21 DTC were diagnosed, mostly papillary thyroid carcinoma (PTC) (81.0%, n=17). Six patients (28.6%) had nodal involvement and one (4.8%) had lung metastasis at the time of the diagnosis. Lymphovascular invasion was present in 11 patients (52.4%). After surgery, 13 patients (61.9%) underwent RAI. The mean follow-up time was 5.7±3.1 years. In total, 6 patients (31.6%) experienced persistent/recurrent disease during the follow-up time. Among PTC patients, persistent/recurrent disease was more frequent in the presence of lymphovascular invasion [55.6% (5/9) vs. 0.0% (0/6), p=0.031]. DISCUSSION AND CONCLUSION: An individualized risk-based approach is recommended. Our study suggests that lymphovascular invasion may be associated with a higher risk of persistence/recurrence and should therefore be considered for decision making in children and adolescents with PTC.